PENGARUH PELATIHAN SIAGA BENCANA MENGGUNAKAN MODUL TERHADAP KESIAPSIAGAAN SISWA MENGHADAPI BENCANA ALAM DI SMA NEGERI 1 BANGLI - I Ketut Suardana; I Made Mertha (Coping: Community of Publishing in Nursing, 2021)
The characteristics of Indonesia's territory consisting of high and low plains, high rainfall and being in a series of "rings of fire" make Indonesia vulnerable to natural disasters. The purpose of this study is to determine the effect of disaster preparedness training on student to facing natural disasters at Senior High School 1 Bangli in 2019. Design of this research is a quasi-experimental study pre and post test with controll group on 74 samples with proportional random sampling technique. Data was collected by questionnaire consisting of 40 items in July - November 2019. Data analysis by paired t test and independent t test with ? = 0.05. The results showed average score for disaster preparedness before the intervention is 65.87 and 73.17 while in the control group 63.91 and 66.14. There is a difference between the preparedness of students facing natural disasters before and after the intervention in the treatment and control group with ? value 0.001 (< ? = 0.05). Disaster preparedness training using modules effected to student preparedness for natural disasters with p value 0.001 (< ? = 0.05). From this research recommended to include disaster preparedness in the local curriculum and concider the value of Balinese culture.